ANALISIS PRAKTIK ASUHAN KEPERAWATAN DENGAN INTERVENSI FINGER HOLD THERAPY UNTUK MENGURANGI NYERI PADA PASIEN INFEKSI LUKA OPERASI (ILO) APPENDIKTOMI DI RUMAH SAKIT BHAYANGKARA TK. I RADEN SAID SUKANTO JAKARTA - Afifah Jihan Ramadhan (2022)
Appendicitis is often found in health care units around the world, the average incidence of acute appendicitis is approximately 100 per 100,000 patients each year in developing countries and includes the highest morbidity rate among other ASEAN countries. One of the medical therapies for the treatment of appendicitis is appendectomy surgery, post-appendectomy patients can experience complications, one of which is surgical wound infection, the average rate of post-appendectomy infection is between 1.2% to 1.6%. The thing that can bother patients with post-appendectomy infection is pain. Pain perception can be overcome by pharmacological and non-pharmacological therapy or a combination of the two. The purpose of providing nursing care is to determine whether the provision of non-pharmacological additional therapy in the form of finger hold therapy can reduce or control pain in post-operative wound infection patients at Bhayangkara TK.I R. Said Sukanto Hospital. The instrument used in measuring the pain scale is the Numeric Rating Scale (NRS). The results obtained in this study, reduced 2 pain scales from a scale of 5 (moderate pain) to a scale of 3 (mild pain) after being given an additional intervention of finger hold therapy for 3 days. In this study it was concluded that finger hold therapy could reduce pain in post-operative wound infection patients appendectomy.